STRATEGI PEWARISAN SENI PERTUNJUKAN DRAMA GONG KEPADA GENERASI PENERUS - Sugita, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This article aims to discuss the inheritance of the performing arts of drama gong to the next generation. As a form of qualitative research, data collection was carried out through analysis of four selected drama gong stories, namely (1) Suluh Ikang Praba; (2) Gesing Reed Beads; (3) Nila Warsiki; and (4) Jayaprana produced in 2019 – 2021. Research data were also collected through observation, document studies, and interviews with several informants who understand the performing arts of gong drama in Bali. Data analysis was carried out qualitatively by applying the theory of semiotics and Bourdeau's social practice. The results of the study indicate that the inheritance of drama gongs is very urgent: (a) to preserve drama gongs; (b) regeneration of young Balinese as supporters of the drama gong; (c) drama gongs are part of Balinese cultural identity, and (d) drama gong as a medium for educating Balinese language and culture. The inheritance of the performing arts of drama gong is carried out through a formal strategy, namely through formal education from kindergarten (PAUD) to college in part by the State Hindu University I Gusti Bagus Sugriwa Denpasar, and an informal strategy, namely the role of families and art-culture studios in socializing, enculturating values. cultural values in the art of performing the drama gong to the younger generation of Bali.